Hybrid Cubic B-spline Method for Solving A Class of Singular Boundary Value Problems (European Journal of Pure and Applied Mathematics, 2023)
In this paper, a class of singular two-point boundary value problems are solved using hybrid cubic B-spline method. In this algorithm, a free parameter γ plays an important role to give accurate converge results for the solution. This parameter are chosen via optimization. Numerical examples are displayed to prove that our suggested method is flexible and effective, and the numerical results are compared with other numerical methods from the literature
Keywords: Singular two-point boundary value problems; Cubic B-spline; Trigono-metric cubic B-spline; Hybrid cubic B-spline